Preserving Karakalpak Traditions - Bekbosinov Esbosin Bekpolatovich (International Journal on Integrated Education, 2023)
Nestled in the western region of Uzbekistan lies the autonomous republic of Karakalpakstan, home to the Karakalpak people. With a rich history dating back centuries, the Karakalpak community proudly upholds their unique traditions, customs, and way of life. This article delves into the vibrant and diverse cultural tapestry of the Karakalpaks, highlighting their distinctive traditions that continue to shape their identity.